ADAPTATION OF UKRAINIAN PUBLIC ADMINISTRATION TO INTERNATIONAL INTEGRATION PROCESSES (EUROPEAN CONTEXT) - MELNYCHUK, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Ukraine's integration with the European Union requires a radical reform of the Ukrainian public administration system by adapting it to the relevant principles of public administration of the European Union. The article identifies six priority areas for public administration reform. The directions for reforming civil legislation are characterized.Improving the quality and efficiency of public administration in Ukraine includes focusing ministries on the formation of state policy; improving the quality of state decisions; clear subordination and delimitation of state functions at the national level; improving the provision of administrative services; forming a professional civil service. The listed areas correspond to the European principles of public administration. The main directions of public administration reform were determined by the Cabinet of Ministers of Ukraine until 2030 in accordance with the recommendations of international organizations.Ukraine's approach to European Union-level service standards is the introduction of general rules for the interaction of the state with citizens and the business community. To this end, 102 electronic services for businesses and citizens are available on the electronic services portal "Diya", and 38 electronic services for businesses and citizens are available through the mobile application "Diya". An up-to-date list of basic electronic services for businesses and citizens is provided. At the same time, an online monitoring system for the quality of administrative services is functioning. The "Trembita" system provides data exchange between state authorities. Most transactions of the "Trembita" system are carried out between the portal "Diya" and the state register of individuals.The transformation of public administration in accordance with international integration processes ensures structured government activities. In a certain part of the central executive bodies, work processes have been optimized through automation in order to bring them into line with international standards. Effective public administration based on strong institutions in the Member States is considered an important prerequisite for achieving the goals, objectives and policies of the EU.
Keywords: European integration; public administration; international integration processes; adaptation of public administration